ANALISIS HARGA POKOK PRODUKSI KOPI PADA PT. FORTUNA INTI ALAM DI DESA MAUMBI KABUPATEN MINAHASA UTARA SULAWESI UTARA - Nevia Asmadi; Agnes Estephina Loho; Jelly Ribka Danaly Lumingkewas (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
This research was conducted for 3 months started from February to April 2019. The data used in this study were primary data and secondary data. Primary data obtained from direct interviews with the general manager of PT. Fortuna Inti Alam using questionnaire. Secondary data is obtained from the companyit selfsuch as history and structure, the Central Bureau of Statistics of Sulawesi Utara, books available at local bookstores and the internet such as Google Search to access articles from various scientific journals and theses from other universities related to this research, especially concerning analysis production cost of goods sold. The results showed that the full costing method had a total of Rp1,919,170,194 or Rp54,295.26/kg and the variable costing method had Rp1,746,450,000 or Rp49,408.83/kg. Difference in comparison of determining the cost of production made by PT.Fortuna Inti Alam with the variable costing method had a difference of Rp172,720,194 or Rp4.886/kg.Keywords: Production cost price , Coffee, PT. Fortuna Inti Alam